2023
DOI: 10.3389/fonc.2023.1133074
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive label-free detection of peritumoral white matter damage using cross-polarization optical coherence tomography

Abstract: IntroductionTo improve the quality of brain tumor resections, it is important to differentiate zones with myelinated fibers destruction from tumor tissue and normal white matter. Optical coherence tomography (OCT) is a promising tool for brain tissue visualization and in the present study, we demonstrate the ability of cross-polarization (CP) OCT to detect damaged white matter and differentiate it from normal and tumor tissues.Materials and methodsThe study was performed on 215 samples of brain tissue obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…They also discovered that certain parameters, such as attenuation and forward cross-scattering, are effective in distinguishing between normal and tumorous brain tissues. Although previous reports have shown that OCT microstructural results can differentiate tumorous from normal brain tissue, the diagnostic accuracy can be further enhanced by utilizing the functional capabilities of OCT [53].…”
Section: Discussionmentioning
confidence: 99%
“…They also discovered that certain parameters, such as attenuation and forward cross-scattering, are effective in distinguishing between normal and tumorous brain tissues. Although previous reports have shown that OCT microstructural results can differentiate tumorous from normal brain tissue, the diagnostic accuracy can be further enhanced by utilizing the functional capabilities of OCT [53].…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of color-coded optical maps emerged as a more promising approach, as it combined the objectivity of optical coefficients with the clarity of visual assessment. This approach substantially improved diagnostic accuracy compared to the visual analysis of structural OCT images [ 86 ]. Bohringer et al conducted a qualitative analysis of OCT images from glial tumors with varying malignancies, identifying signal homogeneity as a key differential criterion.…”
Section: Diagnostic Toolsmentioning
confidence: 99%
“…AI has also been implemented in surgical procedures to assist in the planning phase, aiding in decision-making during surgery. Its utilization has shown promising results, enhancing the accuracy of surgical positioning and mitigating surgical complications [28][29][30][31][32]. In a recent investigation by Tonutti et al, ML was employed to facilitate the diagnosis of intraoperative tumors [32].…”
Section: Tumormentioning
confidence: 99%